Epistemology Of Islamic Education Philosophy: A Conceptual Study Of The Scientific Foundations And Their Implications For Modern Learning - Khasanah, Kharismatul; Khobir, Abdul; Joina, Ceren Desta; Ni’matul Izzati, Arsya Ma’wa; Safitri, Nida Fadhila (AJIRSS: Asian Journal of Innovative Research in Social Science, 2025)
This article examines the epistemology of Islamic education by explaining the role of revelation, reason, experience, and intuition as the main foundations in the formation of knowledge. Unlike Western epistemology, which emphasizes rationality and empirical approaches, Islamic epistemology presents a more holistic perspective because it harmoniously combines spiritual, moral, and intellectual dimensions. This study uses a literature review method, examining various classical and contemporary sources to obtain a more in-depth conceptual overview. The results of the study show that revelation is the highest source of truth, while reason serves as an instrument for understanding reality, and experience and intuition strengthen the process of internalization and application of knowledge in everyday life. This study provides a new perspective by integrating these four sources of knowledge into a single epistemological framework that can be applied in the development of modern learning, thereby emphasizing that today's educational challenges are not only related to technical and methodological aspects but also to strengthening the epistemological foundations that have been neglected. Furthermore, this article highlights the relevance of Islamic epistemology in learning practices through integrated curriculum development, character building, and the use of applicable learning methods. These findings indicate that Islamic epistemology can be an important reference for building a more holistic education that is in line with the needs of the modern era.